Functionality of In vitro Reconstituted Group II Intron RmInt1-Derived Ribonucleoprotein Particles - Molina-Sánchez, Maria D.; García-Rodríguez, Fernando M.; Toro, Nicolás (Frontiers in Molecular Biosciences, 2016)
The functional unit of mobile group II introns is a ribonucleoprotein particle (RNP) consisting of the intron-encoded protein (IEP) and the excised intron RNA. The IEP has reverse transcriptase activity but also promotes RNA splicing, and the RNA-protein complex triggers site-specific DNA insertion by reverse splicing, in a process called retrohoming. In vitro reconstituted ribonucleoprotein complexes from the Lactococcus lactis group II intron Ll.LtrB, which produce a double strand break, have recently been studied as a means of developing group II intron-based gene targeting methods for higher organisms. The Sinorhizobium meliloti group II intron RmInt1 is an efficient mobile retroelement, the dispersal of which appears to be linked to transient single-stranded DNA during replication. The RmInt1IEP lacks the endonuclease domain (En) and cannot cut the bottom strand to generate the 3’ end to initiate reverse transcription. We used an Escherichia coli expression system to produce soluble and active RmInt1 IEP and reconstituted RNPs with purified components in vitro. The RNPs generated were functional and reverse-spliced into a single-stranded DNA target. This work constitutes the starting point for the use of group II introns lacking DNA endonuclease domain-derived RNPs for highly specific gene targeting methods.